THE IMPLEMENTATION OF MINTZBERGâ€™S MANAGERIAL ROLE, A QUALITATIVE STUDY IN â€œSERBUâ€ RETAIL SHOP TOMOHON - Eman, Jilly Gabriella; Pangemanan, Sifrid S.; Pandowo, Merinda (Universitas Sam Ratulangi, 2014)
Manager plays an important role in achieving the goal of an organization. The success can not be separated from active role of a leader in improving human resources performance. Therefore, one of the way for the employees to be more professional and more optimal to do the job is to provide role model to educate and train. The active role of a leader is also necessary to give guidance and direction to employees as well as to supervise their work so that organizational goals can be achieved effectively. The purpose of this study is to determine how the manager's role in improving the performance of employees in reaching the organizational goal and to determine the performance of employees in the company, according to Mintzbergâ€™s Managerial Role, study case in â€œSerbuâ€ Retail Shop Tomohon. The populations observed in this study are the manager and the employees who have been working along with the manager in a period of time as many as 11 respondents. The results based on data collection method processed using the In-Depth Interview. There are three main roles that the manager should play according to Mintzberg which are (1) Interpersonal Role, (2) Informational Role, and (3) Decisional Role. Keywords: Â management, manager, managerial roles